Pemeriksaan Tekanan Darah dan Kolestrol pada Masyarakat Terdampak Bencana Banjir di Desa Wombo Kabupaten Donggala, Sulawesi Tengah - Slamet Ifandi; Andi Lindhemutianingrum Siradje (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Background: Central Sulawesi has experienced a high frequency of natural disasters, with 111 recorded incidents in 2023 and 238 in 2022. The province was also designated as a high-risk disaster area in 2021. Blood pressure and cholesterol screenings are essential tools for diagnosing diseases, identifying risk factors, tracking disease progression, and assessing the effectiveness of treatments. Objective: This initiative aimed to provide free health screenings and offer basic food assistance to the community. Methods: The screenings were conducted in Wombo Village, Tanantovea District, Donggala Regency, Central Sulawesi. Results: The community health screenings revealed that the majority of adults and elderly participants had normal blood pressure and cholesterol levels. However, 5 individuals were found to have high blood pressure, while 20 participants exhibited normal levels. Additionally, 25 individuals had normal cholesterol levels. Conclusion: The screening results indicated that while most participants were in good health, a small percentage had elevated blood pressure, which warrants further attention. This initiative successfully provided free healthcare services and essential food support to the community.